Mosque capital accounting practices: A local wisdom perspective of Indonesia - Thalib, Mohamad Anwar (JIFA (Journal of Islamic Finance and Accounting), 2023)
This research departs from the problem of adopting and implementing capital accounting that was born from modernity, which impacts the increasingly marginalized local cultural values of capital accounting practices. In addition, studies on capital accounting based on local wisdom in the context of places of worship (mosques) are rare. This study aims to reveal the local cultural values behind the practice of mosque capital accounting in Gorontalo Indonesia. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: analysis of charity, knowledge, science, revelation information, and good deeds. The results of the study found that there were three capital accounting practices, namely capital accounting practices sourced from the community, capital accounting practices sourced from the government, and capital accounting practices sourced from private companies. Local cultural values drive the practice of capital accounting in the form of paracaya. This paracaya value is reflected through the actions of mosque administrators who report the income and expenses of the mosque's capital every week. This action is an effort to maintain a sense of trust between donors, worshipers, and the community in managing the mosque capital. The value of paracaya is often expressed by parents in Gorontalo through lumadu "dahayi moputu dila" which means to keep your tongue from breaking. This study concludes that mosque administrators practice capital accounting based on local cultural values in the form of paracaya. This research contributes to presenting capital accounting practices based on the local Gorontalo culture.